Efeito da metilprednisolona na lesão de isquemia e reperfusão renal - Fernandes-charpiot, Ida Maria Maximina (2011)
Introduction: Renal ischemia is the most important cause of acute kidney injury (AKI). Methylprednisolone (MP) has been shown to give protection against ischemia/reperfusion injury (I/R) in the liver and the heart. Objective: To examine a possible protective role of MP in renal I/R. Methods: Male Wistar rats were treated with 30mg/kg of intravenous MP or saline 1 hour before unilateral renal ischemia (RI), which lasted for 30 minutes. The animals were divided into 3 groups (8 in each group): Sham (sham surgery without RI), Vehicle (Veic)-I/R (saline infusion followed by RI), and the MP-I/R group (MP infusion followed by RI). The glomerular filtration rate (GFR) - which is inulin clearance in ml/min/100g, sodium fractional excretion (FENa), urinary osmolality, and histological analysis were assessed 2 days after RI. Additionally, immunohistochemical staining (2 days after RI) was performed to measure macrophages (ED-1 positive cells), neutrophils (No), and lymphocytes (Lo) and the nuclear factor-κB (NFκ-B). Results are expressed as mean ± SD, and were compared by ANOVA, followed by Bonferroni test, with p < 0.05. Results: GFR was 0.92 ± 0.30 ml/min/100g in the MP-I/R group, 0.90 ± 0.27 ml/min/100g in the Sham group, and 0.47 ± 0.24 ml/min/100g in the Veic-I/R group (p < 0.05 vs. MP-I/R and Sham). The FENa was similar in the MP-I/R (0.19%) and Sham groups (0.35%, NS), and higher in the Veic-I/R group (0.62%, p < 0.05 vs. MP-I/R). Urinary osmolality was similar between the 3 groups. Acute epithelial degenerative changes and tubular dilatation were significantly more intense in the Veic-I/R group than the MP-I/R and Sham groups. Only the Veic-I/R group presented with focal acute tubular necrosis. In the cortex, the number of Lo was significantly greater in the Veic-I/R group when compared with the Sham and MP-I/R groups (14.36 ± 3.32 vs. 6.75 ± 1.18 and 5.31 ± 1.63, respectively, p < 0.05 Veic-I/R vs. Sham and MP-I/R) and in the outer medulla (OM) areas (10.58 ± 3.04 vs. 4.51 ± 1.29 and 3.70 ± 0.62, p < 0.05 Veic-I/R vs. Sham and MP-I/R). The number of macrophages was also significantly greater in the Veic-I/R group (9.84 ± 3.18) when compared with Sham (4.65 ± 1.12, p < 0.05) and MP-I/R groups (4.06 ± 1.84, p < 0.05). Similarly, the number of No in the OM was 3.13 ± 2.09 in Veic-I/R vs. 0.74 ± 0.51 in Sham group, and 1.44 ± 1.11 in the MP-I/R group (p < 0.05). The NFκ-B expression was more intense in the OM in the Veic-I/R group compared with the Sham and in the MP-I/R groups (0.61 ± 0.33 vs. 0.03 ± 0.03 and 0.12 ± 0.11 respectively, p < 0.05). Conclusion: The pretreatment with high doses of MP conferred striking protection against renal I/R. This protection effect was related to the modulation of I/R-induced inflammatory mechanisms and to inflammatory cell infiltration triggered by I/R.